Income Tax In Manufacturing Companies On The Indonesia Stock Exchange Viewed From Variables - Vidya Muliyani; Andi Irfan* (IAIN Palopo, 2023)
This study aims to determine the effect of cost of production, profitability, inventory, net sales and operating costs on corporate taxpayer income tax in manufacturing companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange (IDX) in 2017-2020. This type of research is quantitative. Sampling used a purposive sampling technique and a sample of 30 manufacturing companies in the basic and chemical industries were listed on the Indonesia Stock Exchange (IDX) for 2017-2020. The data analysis method was performed by panel data regression analysis with the help of the Eviews 10 statistical tool. The regression model used was the random effect model using the classical assumption test, hypothesis test, and r-squared test. The results showed that the cost of production, profitability, net sales, operating costs have a positive effect on corporate income tax. While inventory has no positive effect on corporate income tax. The R2 value indicates that the contribution of all independent variables in explaining the dependent variable is 87.54%, while the remaining 12.46% is explained by other variables not measured in this regression model.